Co-Ni Basic Carbonate Nanowire/Carbon Nanotube Network With High Electrochemical Capacitive Performance via Electrochemical Conversion - Tan, Furui; Chen, Hongyuan; Yuan, Ronghua; Zhang, Xuming; Chen, Deliang (Frontiers in Chemistry, 2021)
In this work, the Co-Ni basic carbonate nanowires were in-situ grown on carbon nanotube (CNT) network through a facile chemical bath deposition method, which could be further converted into active hydroxide via cyclic voltammetry strategy. A series of carbonate nanowire/nanotube with different Co/Ni ratio revealed the different growth status of the nanowires on CNT network. The nanostructures of the as-synthesized samples were examined via powder X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM) techniques. The Co/Ni ratio of the carbonate largely affected the size of the nanowires, that the low Co/Ni ratio was beneficial for thin nanowire formation and the nanowires loading on CNT network. Subsequently, the electrochemical performance of the Co-Ni basic hydroxides was studied in a three-electrode test system. The nanowires with low Co/Ni ratio 1/2 can form nanowire array on individual CNTs, which exhibited better electrochemical capacitive performance than the composite network with high Co/Ni ratio nanowires after electrochemical activation. This result is valuable for the design of inorganic electrochemical active composites based on conductive networks for energy conversion/storage applications.